2022
DOI: 10.1007/s00125-022-05829-9
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Acat2 overexpression promotes systemic cholesterol metabolism and adipose lipid metabolism in mice

Abstract: Aims/hypothesis Acetyl coenzyme A acetyltransferase (ACAT), also known as acetoacetyl-CoA thiolase, catalyses the formation of acetoacetyl-CoA from acetyl-CoA and forms part of the isoprenoid biosynthesis pathway. Thus, ACAT plays a central role in cholesterol metabolism in a variety of cells. Here, we aimed to assess the effect of hepatic Acat2 overexpression on cholesterol metabolism and systemic energy metabolism. Methods We generated liver-targeted ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…Furthermore, elevated serum glucose levels have been implicated in increasing substrate concentrations across various metabolic pathways. This enhances the synthesis of TG and TC in serum, factors integral to growth, development, and metabolism, as supported by studies from Ma et al [44] and Schade et al [45]. A noteworthy aspect of our study is the Spearman analysis, which revealed a simultaneous and positive correlation between glucose, TG, and TC and the relative abundance of specific rumen bacteria, namely Prevotellaceae_UCG-001 and Prevotellaceae_UCG-004.…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, elevated serum glucose levels have been implicated in increasing substrate concentrations across various metabolic pathways. This enhances the synthesis of TG and TC in serum, factors integral to growth, development, and metabolism, as supported by studies from Ma et al [44] and Schade et al [45]. A noteworthy aspect of our study is the Spearman analysis, which revealed a simultaneous and positive correlation between glucose, TG, and TC and the relative abundance of specific rumen bacteria, namely Prevotellaceae_UCG-001 and Prevotellaceae_UCG-004.…”
Section: Discussionsupporting
confidence: 84%
“…However, very little is known about other mechanisms. Recently, a new study has shown that the inflammatory responses or liver stress resulting from ACAT2 overexpression also inhibit the metabolic pathways of glycolytic, TG synthesis, mitochondrial‐related and ketone body metabolism, but the upregulated genes participate in the metabolism of cholesterol, particularly the biosynthesis pathway of bile acid 15 . ACAT2 is significantly upregulated, and promotes cancer cell growth and progression of CRC 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Last, we used KO mice to perform in vivo loss-of-function studies of SLC36A2 and SLC36A3. However, the gain-of-function study through generating overexpression models, especially tissue specific overexpression by transgenic mice or virus injection are still required [ 48 , 49 ]. Thus, future efforts which focus on the tissue specificity of SLC36As will be the next direction.…”
Section: Discussionmentioning
confidence: 99%